Social identity as a key concept for connecting transformative societal change with individual environmental activism. (December 2020) - Schulte, Maxie; Bamberg, Sebastian; Rees, Jonas; Rollin, Philipp
Abstract: This paper proposes social identity as a psychological concept that connects societal and individual aspects of transformation processes. To this end, we embed the social identity concept into the multilevel perspective, a framework frequently used for analysing societal transformation processes. The paper presents three meta-analyses summarizing the empirical evidence for the postulated strong pro-environmental social identity-pro-environmental collective action link. A first meta-analysis (nine samples) finds a pooled correlation of r + = .63 between pro-environmental social identity and intention to participate in pro-environmental collective action. This finding is replicated in a second meta-analysis, which shows a correlation of r + = 0.56 (15 samples). The third meta-analysis supports that pro-environmental social identity is a stronger predictor of collective pro-environmental action than of individual pro-environmental private-sphere behavior ( r + = 0.35; eight samples). We discuss implications of these findings for further research and highlight power and ideology as additional transformation-oriented psychological constructs. Highlights: Social identity connects societal and individual aspects of transformation. Meta-analyses support the link between opinion-group based social identity and pro-environmental collective action. Environmental psychology can contribute to the interdisciplinary perspective on transformation.